Synthetic and Crystallographic Insight into Exploiting sp2 Hybridization in the Development of α‐l‐Fucosidase Inhibitors. (18th March 2019) - Coyle, Travis; Wu, Liang; Debowski, Aleksandra W.; Davies, Gideon J.; Stubbs, Keith A.
Abstract: The sugar fucose plays a myriad of roles in biological recognition. Enzymes hydrolyzing fucose from glycoconjugates, α‐l ‐fucosidases, are important targets for inhibitor and probe development. Here we describe the synthesis and evaluation of novel α‐l ‐fucosidase inhibitors, with X‐ray crystallographic analysis using an α‐l ‐fucosidase from Bacteroides thetaiotamicron helping to lay a foundation for future development of inhibitors for this important enzyme class. Abstract : Perfect fit : Enzymes hydrolyzing fucose from glycoconjugates, α‐l ‐fucosidases, are important targets for inhibitor and probe development. The synthesis and evaluation of novel α‐l ‐fucosidase inhibitors, with X‐ray crystallographic analysis are presented.